2003
DOI: 10.1191/0269216303pm693oa
|View full text |Cite
|
Sign up to set email alerts
|

The development of palliative care in national government policy in England, 1986–2000

Abstract: Palliative care is an established and expanding speciality, important in many areas of service delivery within health and social services and the voluntary sector. Traditionally, palliative care is viewed as most closely linked to cancer services. National government policy has an inevitable impact on the organization and provision of such services. As part of a wider project, an investigation of the content and development of English government policy relating to palliative care was carried out. The developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…Improving a health care system so that it can deliver better breast health care can best be accomplished if multiple sectors act in collaboration (67); that is, improvements are most likely to be achieved when health care ministries and governmental agencies, nongovernmental organizations (NGOs), and public and patient groups work together (24,68,69). The relative contribution of each sector will depend on the country's governmental structure, the extent of focus on health care and breast cancer, available resources, the strength of the NGO sector, and the ability of patients, survivors, and advocates to “raise their voices.” Women's health advocacy and consumerism have had a direct impact on oncology care in the United States, having the greatest effect when the activities of advocates and health care professionals are coordinated and aligned to guide policymakers toward effective and desirable change (68).…”
Section: Recommendationsmentioning
confidence: 99%
“…Improving a health care system so that it can deliver better breast health care can best be accomplished if multiple sectors act in collaboration (67); that is, improvements are most likely to be achieved when health care ministries and governmental agencies, nongovernmental organizations (NGOs), and public and patient groups work together (24,68,69). The relative contribution of each sector will depend on the country's governmental structure, the extent of focus on health care and breast cancer, available resources, the strength of the NGO sector, and the ability of patients, survivors, and advocates to “raise their voices.” Women's health advocacy and consumerism have had a direct impact on oncology care in the United States, having the greatest effect when the activities of advocates and health care professionals are coordinated and aligned to guide policymakers toward effective and desirable change (68).…”
Section: Recommendationsmentioning
confidence: 99%
“…Perhaps this refl ects differences in access to tertiarybased palliative care services, which traditionally grew from, and remains most closely associated with, cancer services. 24 There are numerous studies that have examined whether health care expenditure is driven by a person's age or their proximity to death. A useful summary is provided by Gray, who concluded that "… the relationship between age and health expenditure was weak and possibly inverse once proximity to death was allowed for".…”
Section: Vulnerable Peoplementioning
confidence: 99%
“…Only a relatively small number of empirical studies have been conducted on administrativerelated issues. Since the palliative care movement began in England, several studies have examined funding and access issues in the United Kingdom (cf., Matthew, Cowley, Bliss, & Thistlewood, 2003;Sims, 1995;Wood, Clark, & Gatrell, 2004). A couple of studies have examined similar funding and utilization issues in the United States (cf., Han et al, 2006;Huskamp, Buntin, Wang, & Newhouse, 2001).…”
mentioning
confidence: 98%